A method and apparatus for producing a copper-titanium alloy slab
Patent Information
- Application Number
- CN202611004897.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-11-03
AI Technical Summary
Traditional copper-titanium alloy slab preparation processes suffer from problems such as complex equipment structure, high operation and maintenance costs, large melt temperature loss, and low material yield. This is especially true in continuous casting technology using tundishes, which leads to low production efficiency and uneven material properties.
The process employs an integrated vacuum induction casting process without a tundish. By adding cathode copper and copper-titanium master alloys in successive furnaces, combined with stepped heating power control, electromagnetic stirring and inert gas protection, the alloy melt is directly introduced into the forming mold for continuous casting. With the assistance of staged cooling water flow control, large-size slabs can be prepared.
This technology enables direct continuous casting of large-size copper-titanium alloy slabs, shortening the production cycle, improving production efficiency, reducing energy consumption and production costs, increasing material utilization, and ensuring the compositional uniformity and quality of the finished product.
Smart Images

Figure CN123027461A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of metal material preparation technology, and in particular to a method and apparatus for preparing copper-titanium alloy slabs. Background Technology
[0002] Copper-titanium alloys possess high strength, high elasticity, high conductivity, and excellent corrosion resistance, making them an important raw material for manufacturing electrical switches, elastic components, and other products. Their overall performance is comparable to copper-beryllium alloys, and they are environmentally friendly and non-toxic. Titanium resources are abundant, applications are continuously expanding, and market demand is growing daily.
[0003] Traditional copper-titanium alloy slab preparation processes typically involve multiple steps, including vacuum melting, casting, billet preparation, hot rolling, and cold rolling. The entire process is lengthy, with a production cycle of 3-5 days. During billet preparation and rolling, the high strength and hardness of copper-titanium alloys make processing difficult, easily leading to defects such as surface cracks and edge cracking, resulting in a low yield, generally only 70%-75%. Furthermore, multiple heating stages not only increase energy consumption but also easily cause segregation of copper and titanium elements, affecting the uniformity of material properties.
[0004] To address the problems of traditional processes, continuous casting technology has been employed in existing technologies. However, current continuous casting processes typically require an tundish between the vacuum melting furnace and the crystallizer to store and regulate the melt flow. While this design enables continuous production, it also introduces significant drawbacks: First, the presence of the tundish significantly increases the structural complexity of the equipment, raising not only investment costs but also the difficulty and expense of daily maintenance. Second, the melt experiences substantial temperature loss as it flows through the tundish, typically dropping by 30-50°C. To ensure the melt temperature entering the crystallizer meets requirements, the melting temperature needs to be increased, further increasing energy consumption. Furthermore, as an additional melt contact vessel, the tundish may also increase the risk of melt contamination. Summary of the Invention
[0005] The main purpose of this application is to provide a method and apparatus for preparing copper-titanium alloy slabs, which aims to solve the problems of complex equipment structure, high operation and maintenance costs, and large melt temperature loss caused by the reliance on tundishes in existing continuous casting technology.
[0006] To achieve the above objectives, this application provides a method for preparing a copper-titanium alloy slab, comprising the following steps: The raw materials are added in batches, one furnace at a time, and include cathode copper and copper-titanium master alloy. The cathode copper is placed in the melting chamber, and the melting chamber is evacuated to a pressure of 0.1 Pa to 10 Pa. The chamber is heated using a stepped heating power control method until the cathode copper is completely melted to obtain a melt. The copper-titanium master alloy is added to the melt. When the master alloy melts completely and the temperature rises to 1250℃-1350℃, it is refined for 10-30 minutes. After refining, the mixture is stirred to obtain an alloy melt. The alloy melt is then introduced into a forming mold through a guide channel and continuously cast under an inert gas protective atmosphere to obtain a slab. The total flow rate of cooling water on the large surface, the total flow rate of cooling water on the small surface, and the total flow rate of secondary cooling water of the forming mold are controlled to allow the slab to gradually cool and solidify, thereby obtaining the copper-titanium alloy slab.
[0007] Optionally, the stepped heating power control method includes: the initial heating power is 30%-40% of the total power, after holding the temperature for 10-20 minutes, the power is increased to 50%-60% of the total power, held for 10-15 minutes, and finally the power is increased to 70%-80% of the total power until the material is completely melted.
[0008] Optionally, during the refining process, an electromagnetic stirring device is used for stirring, with a stirring power of 5kW-15kW and a stirring time of 5-10 minutes.
[0009] Optionally, the flow channel is pre-baked at a temperature of 200℃-300℃ for 2-4 hours.
[0010] Optionally, the inert gas is argon or helium, and the flow rate of the inert gas introduced into the molding die is controlled to be 5L / min-15L / min.
[0011] Optionally, the total flow rate of cooling water for the large surface of the molding die is controlled at 800L / h-1200L / h, and the total flow rate of cooling water for the small surface is controlled at 400L / h-600L / h.
[0012] Optionally, the total flow rate of the secondary cooling water is controlled at 300L / h-500L / h, and the slab solidification is gradually cooled by spray cooling and air cooling in sequence.
[0013] Optionally, the purity of the cathode copper is ≥99.95%, and the titanium content in the copper-titanium master alloy is 20wt%-30wt%.
[0014] In addition, to achieve the above objectives, this application also provides a copper-titanium alloy slab preparation apparatus for realizing the above-mentioned copper-titanium alloy slab preparation method, including a vacuum melting apparatus, a continuous casting forming apparatus and a cooling and solidification apparatus. The discharge port of the vacuum melting apparatus is directly connected to the inlet of the continuous casting forming apparatus through a guide channel. The continuous casting forming apparatus includes a graphite forming mold and an argon gas protection system.
[0015] Optionally, the flow channel is equipped with a baking preheating device, the molding die is connected to a cooling water control system and a secondary cooling device, and the vacuum melting device is equipped with an electromagnetic stirring device.
[0016] Compared with the prior art, this application has the following beneficial effects: (1) This application can realize direct continuous casting of large-size slabs, break through the technical bottleneck, abandon the intermediate ladle design, and directly introduce the melt into the crystallizer, which can be directly cast into large-size slabs with a thickness of 150mm-200mm and a width of 500mm-600mm, greatly expanding the application scenarios of copper-titanium alloy slabs. 2. This application adopts an integrated vacuum induction continuous casting process without tundish, which eliminates the traditional multiple processes and shortens the production cycle from the traditional 24h-48h to 8h-10h, increasing production efficiency by more than 60%, enabling large-scale continuous production and significantly saving time costs. 3. This application adopts an integrated continuous casting process to reduce multiple heating and rolling processes, which can reduce energy consumption by 30%-45%; the raw material utilization rate is increased to over 90%, avoiding material loss during the billet making process, and reducing the overall production cost by 25%-40%. Attached Figure Description
[0017] Figure 1 This is a flowchart of the method for preparing copper-titanium alloy slabs in the embodiments of this application; Figure 2 This is a schematic diagram of the copper-titanium alloy slab preparation apparatus in the embodiments of this application; Figure 3 This is a microstructure diagram of the copper-titanium alloy slab prepared in Example 3 of this application. Figure 4 This is a power-time curve of the stepped heating power control method in the embodiments of this application; Figure 5 This is a schematic diagram of the cooling water flow distribution of the cooling control system in an embodiment of this application. Detailed Implementation
[0018] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0019] Reference Figure 1 This application provides a method for preparing a copper-titanium alloy slab, comprising the following steps: S1. The raw materials are added in batches one furnace at a time, including cathode copper and copper-titanium master alloy.
[0020] The purity standard for the cathode copper raw material is ≥99.95%, with Grade A electrolytic cathode copper being preferred. The low-impurity substrate reduces oxides and non-metallic inclusions in the melt. A matching copper-titanium master alloy is used, with a titanium content preferably between 20wt% and 30wt%. Unlike high-titanium master alloys, this alloy exhibits a moderate melting rate within this range, facilitating the uniform dissolution of titanium into the copper matrix and preventing the formation of coarse and brittle second phases due to excessively high local titanium concentrations.
[0021] S2. Place the cathode copper in the melting chamber, evacuate the melting chamber to a pressure of 0.1Pa-10Pa, and heat it using a stepped heating power control method until the cathode copper is completely melted to obtain the melt.
[0022] After the ingredients are prepared, all the cathode copper is placed inside the melting chamber beforehand, and the copper-titanium intermediate alloy is stored separately in a special sealed feeding box. It is added in batches after the cathode copper is completely melted to prevent the titanium from being burned by premature contact with the high temperature vacuum environment.
[0023] First, the vacuum melting chamber is evacuated, and the pressure is controlled within the range of 0.1Pa-10Pa. The vacuum environment isolates oxygen and water vapor, inhibiting the oxidation and burning loss of active titanium. A stepped heating power control method is used for heating to avoid local overheating and splashing of copper material and excessive thermal stress on the furnace body caused by a one-time high-power heating.
[0024] S3. Add the copper-titanium master alloy to the melt. When the master alloy melts completely and the temperature rises to 1250℃-1350℃, refine it for 10-30 minutes.
[0025] The refining time is 10-30 minutes. Within this temperature range, the melt has good fluidity and will not increase the loss of titanium volatilization due to excessive temperature. Electromagnetic stirring is carried out simultaneously during the refining stage. The electromagnetic force drives the melt to circulate and disperse local high titanium enrichment areas, eliminate macroscopic segregation of titanium elements in advance, and drive the bubbles inside the melt to rise and be discharged, reducing the porosity defects of the billet.
[0026] S4. After refining, the mixture is stirred to obtain an alloy melt. The alloy melt is then introduced into a forming mold through a guide channel and continuously cast under an inert gas protective atmosphere to obtain a slab.
[0027] This application eliminates the traditional tundish buffer structure. The discharge port of the smelting furnace is directly connected to the forming mold through a guide channel, which can directly cast large-size slabs with a thickness of 150mm-200mm and a width of 500mm-600mm, greatly expanding the application scenarios of copper-titanium alloy slabs.
[0028] S5. Control the total flow rate of cooling water on the large surface of the forming mold, the total flow rate of cooling water on the small surface, and the total flow rate of secondary cooling water to gradually cool and solidify the slab to obtain a copper-titanium alloy slab.
[0029] By controlling the flow rate of cooling water in stages, and combining spray and air cooling modes, the heat of solidification of the slab is slowly released, avoiding internal cracks and surface deformation caused by excessive temperature difference between the inside and outside of the thick slab.
[0030] In other embodiments, the stepped heating power control method mentioned in step S2 includes: the initial heating power is 30%-40% of the total power, after holding for 10-20 minutes, the power is increased to 50%-60% of the total power, held for 10-15 minutes, and finally the power is increased to 70%-80% of the total power until the material is completely melted.
[0031] This embodiment employs a three-stage, step-by-step heating method, which differs from the one-time full-power heating mode. It is primarily designed to address the characteristics of the cathode copper raw material and the features of the closed environment of vacuum melting, thus solving three types of practical production problems: First, the cathode copper surface adsorbs water vapor, oil, and air. High-power direct heating can easily cause water vapor to expand rapidly, resulting in melt splashing and a sudden increase in furnace pressure, which can destroy the vacuum environment. Secondly, the entire cathode copper has slow thermal conductivity. Heating at full power at once can cause local overheating and melting, and large copper cores may not melt for a long time. The asynchronous melting prolongs the smelting time. Third, the induction coils and crucible refractory materials of the vacuum furnace are subjected to excessive thermal shock. Frequent rapid heating and cooling will accelerate the cracking of the inner lining and the aging of the coil, increasing equipment wear and tear. By using power-divided and staged heat preservation, heat is released slowly, taking into account the triple requirements of degassing, stable melting, and furnace protection.
[0032] This embodiment uses a three-stage, step-by-step heating method, such as... Figure 4 As shown: The first stage heating power is 30%-40% of the total power, and the holding time is 10-20 minutes. The reasons are as follows: low power output results in gentle heat, and the overall temperature inside the furnace rises slowly, preventing a rapid increase in the copper melting point. If the power is below 30%, the heating rate is too slow, the degassing efficiency is low, and the overall smelting cycle is prolonged. If the power is above 40%, the temperature rises too quickly, and the surface water vapor vaporizes instantly, which can easily cause a sudden pressure increase in the furnace cavity and disrupt the vacuum. Holding time for at least 10 minutes ensures that the surface of large copper pieces is fully dried, and for thicker copper pieces, this can be extended to 20 minutes to ensure thorough dehydration.
[0033] The reason for increasing the power to 50%-60% of the total power in the second stage and holding it at that temperature for 10-15 minutes is that with continuous heating at a medium power, the furnace temperature gradually approaches the melting point of pure copper. The edges and thinner pieces of the cathode copper soften and melt locally first. Gradually melting the edges and corners of the cathode copper forms a small amount of liquid copper. Relying on the heat conduction of the liquid copper accelerates the heat transfer of the entire cathode copper, avoiding the "melted outside, solid inside" layering state of large solid cathode copper pieces.
[0034] The third stage increases the power to 70%-80% of the total power until the material is completely melted. The reason is that after the first two stages of preheating and premelting, a stable liquid copper pool has been formed in the furnace, and the thermal conductivity has been greatly improved, which allows for increased power to accelerate the melting of the remaining cathode copper. After the molten pool is formed, the heat conduction is uniform, and there will be no local overheating. Since titanium has not been added, there is no risk of high-temperature burn-off.
[0035] In other embodiments, during step S3, an electromagnetic stirring device can be used for stirring during the refining process. The stirring power is 5kW-15kW, and the stirring time is 5-10 minutes. Simultaneous electromagnetic stirring during the refining stage drives the overall flow of the melt using electromagnetic force, breaking up localized areas of titanium enrichment and reducing component segregation. At the same time, stirring the melt causes internal bubbles to rise and escape, reducing porosity defects in the cast billet.
[0036] In other embodiments, the flow channel mentioned in step S4 is pre-baked at a temperature of 200°C-300°C for 2-4 hours. The purpose is to remove the moisture and residual oil adsorbed on the inner wall of the flow channel, prevent the high-temperature melt from oxidizing and producing pores when it comes into contact with the cold wall and encounters water vapor; at the same time, it reduces the temperature drop of the melt flowing through the channel, and avoids the melt from solidifying prematurely and blocking the flow channel.
[0037] In other embodiments, the inert gas mentioned in step S4 is argon or helium, and the flow rate of the inert gas introduced into the forming mold is controlled to be 5L / min-15L / min. Using an inert gas as a protective gas can isolate air, inhibit the reaction of active titanium with oxygen and water vapor, and reduce oxidation inclusions in the cast billet. Argon is cheaper and is the preferred choice for industry; helium has a better protective effect and is suitable for the production of high-cleanliness, high-end sheet metal.
[0038] In other embodiments, the total flow rate of cooling water on the large surface of the forming mold can be controlled at 800L / h-1200L / h, and the total flow rate on the small surface can be controlled at 400L / h-600L / h. The large surface of the forming mold has a larger contact area with the melt and a higher heat load, requiring a larger cooling water volume to ensure uniform growth of the solidified shell around the slab, avoiding leakage from a thin shell on one side and uneven slab thickness. If the water volume on the large surface is less than 800L / h, the cooling intensity is insufficient, and the slab shell becomes too thin, prone to bulging and deformation; if it is more than 1200L / h, the cooling is too rapid, resulting in a large temperature difference between the inside and outside of the slab shell, easily causing surface cracks. The small surface of the forming mold has a small heat dissipation area, requiring half the water volume to meet heat dissipation needs, which can easily lead to corner cracking or slow solidification outside this area.
[0039] In other embodiments, the total flow rate of the secondary cooling water can be controlled to be 300L / h-500L / h, and the slab solidification can be gradually cooled by spray cooling and air cooling in sequence.
[0040] After the slab leaves the forming mold, the large temperature difference between the inside and outside can easily cause internal thermal cracks if directly and forcefully cooled. A gradual cooling method using spraying and air cooling can be employed to release solidification heat evenly from the surface inwards, reducing internal stress and minimizing warping and cracking defects. Spraying first achieves rapid surface shaping, followed by slow air cooling to release heat from the core; this gradient cooling method is well-suited to the solidification characteristics of thick copper-titanium slabs.
[0041] In other embodiments, the purity of the cathode copper is ≥99.95%, and the titanium content in the copper-titanium master alloy is 20wt%-30wt%.
[0042] A cathode copper purity of ≥99.95% significantly reduces the introduction of impurities such as lead, iron, and oxygen into the melt, minimizing non-metallic inclusions and porosity, and ensuring stable electrical conductivity and elasticity of the alloy. Insufficient purity leads to impurities easily forming brittle compounds with titanium, reducing the mechanical properties of the finished product. The titanium content in the copper-titanium master alloy is 20wt%-30wt%, indicating a suitable melting rate within this range. After being added to the melt, it can quickly and uniformly dissolve into the copper matrix, minimizing the formation of coarse titanium compounds. High-titanium master alloys are prone to localized agglomeration, while low-titanium master alloys require large addition amounts, increasing smelting time and energy consumption.
[0043] like Figure 2 As shown, this application provides a copper-titanium alloy slab preparation apparatus and a method for preparing copper-titanium alloy slabs. The entire apparatus consists of four main modules: a vacuum melting device 1, a flow channel 2, a continuous casting forming device 3, and a cooling and solidification device 4. The connection relationships and functions of each component are described below: The vacuum melting device 1 has a built-in electromagnetic stirring mechanism 5, which can perform electromagnetic stirring on the melt during the melting and refining stages; the cavity is equipped with a vacuum pumping system 6, a stepped power controllable induction heating system 7, and an independent sealed feeding box 8, realizing integrated operation of vacuum melting, alloying, and in-furnace refining; the outlet of the vacuum melting device 1 has no intermediate ladle interface and is directly connected to the guide channel 2.
[0044] The guide channel 2 serves as a direct transition channel between the vacuum melting device 1 and the forming mold 9. It is equipped with an independent baking and preheating device 10, which can preheat the inner wall of the channel at a constant temperature to remove water. The inner wall of the channel is made of high-temperature resistant and fire-resistant material to reduce melt adhesion and impurity shedding.
[0045] The main body of the continuous casting forming device 3 is a forming mold 9 made of graphite composite material, which is matched with the casting requirements of large-size slabs; it is equipped with an argon / helium inert gas supply system 11, which continuously supplies protective gas into the forming mold 9 to isolate it from air oxidation.
[0046] The cooling and solidification device 4 includes a cooling water control system 12 and a secondary cooling device 13. The cooling water control system 12 separately controls the flow rate of independent water channels on the large and small faces of the mold. The secondary cooling device 13 integrates a spray cooling component 1301 and an air-cooling mechanism 1302, which can adjust the cooling water volume and air speed in stages to achieve gradient slow cooling. A schematic diagram of the cooling water flow distribution of the cooling water control system 12 in this application is shown below. Figure 5 As shown.
[0047] The outlet of the vacuum melting device 1 is directly connected to the inlet of the casting device 3 via the flow guide channel 2, eliminating the need for intermediate ladle components throughout the process. This simplifies equipment pipelines and associated insulation and flow control structures, reducing equipment procurement and subsequent maintenance costs. This device enables an integrated vacuum induction continuous casting process without an intermediate ladle, eliminating traditional multi-step processes. The production cycle is shortened from the traditional 24-48 hours to 8-10 hours, increasing production efficiency by over 60%. It allows for large-scale continuous production, significantly saving time and costs.
[0048] Example 1 This embodiment provides a method for preparing copper-titanium alloy slabs using the above-described apparatus, including: 1. Pre-treatment of equipment before production Baking and preheating of the flow channel: Start the baking and preheating device 10 of the flow channel 2, set the baking temperature to 250℃, bake at a constant temperature for 3 hours, and maintain the preheating and heat preservation state after baking to thoroughly remove the adsorbed moisture and residual oil on the inner wall of the channel, so as to avoid oxidation and blockage when the melt flows through. Inspection of smelting equipment: Clean the debris inside the vacuum smelting device 1, test the vacuum pumping system 6, the stepped power controllable induction heating system 7, the electromagnetic stirring mechanism 5, and confirm that the feeding box 8 is sealed and leak-free. Continuous casting and cooling system commissioning: Check that the air supply system 11 of the continuous casting forming device 3 is unobstructed; commission the cooling water control system 12 of the cooling and solidification device 4, confirm that there is no leakage in the independent water circuits and secondary cooling water circuits of the large and small faces of the forming mold, and test that the spray cooling component 1301 and the air cooling mechanism 1302 can be adjusted normally.
[0049] 2. Ingredient preparation and feeding Grade A electrolytic copper with a purity of 99.9935% was selected as the base material, and copper-titanium master alloy with a Ti mass fraction of 48% was selected as the alloying material. The raw materials were weighed according to the target Ti content of 3.3wt% and the balance Cu. All Grade A electrolytic copper was put into the furnace cavity of vacuum melting device 1, and the copper-titanium master alloy was stored in the feeding box 8 and the sealing valve was locked to prevent premature contact with the high temperature environment inside the vacuum furnace, which would cause titanium to burn off.
[0050] 3. Vacuum stepped heating smelting Start the vacuum pumping system 6 and continue to pump the vacuum until the pressure in the melting chamber stabilizes at 5Pa. Rely on the vacuum environment to isolate air and moisture and inhibit the oxidation of active titanium. The stepped power controllable induction heating system 7 is activated to melt copper in a segmented gradient heating manner. The initial power is set to 35% of the total power, and the temperature is maintained for 15 minutes for low-temperature degassing and dehydration. Increase the power to 55% of the total power, hold the pre-melted copper material at a temperature of 12 minutes to form a small amount of liquid copper to accelerate heat transfer; Increase the power to 75% of the total power and continue heating until the solid cathode copper in the furnace is completely melted, resulting in pure copper melt.
[0051] 4. Alloying, refining and electromagnetic stirring Open the charging tank 8 and add the copper-titanium master alloy to the pure copper melt in batches. After the master alloy has completely melted and the melt temperature has stabilized at 1280℃, proceed with refining for 35 minutes. After refining, start the electromagnetic stirring mechanism 5 in the furnace with a stirring power of 10kW and stir continuously for 12 minutes. Rely on electromagnetic convection to disperse the local enrichment areas of titanium elements, and at the same time promote the bubbles inside the melt to rise and be discharged, reducing the porosity defects of the billet.
[0052] 5. Tundish-free direct-connection inert atmosphere continuous casting Start the gas supply system 11 to continuously introduce argon gas into the graphite composite molding die 9 (such as a graphite-copper composite molding die) at a stable flow rate of 10L / min, forming a complete inert protective atmosphere in the molten pool area of the crystallizer.
[0053] The vacuum melting device 1 slowly tilts the furnace body, and the alloy melt flows by its own weight through the guide channel 2 which is preheated at 250°C for 3 hours, and flows directly into the forming mold 9 without intermediate ladle transfer; The cooling parameters of the molding die are set by the cooling water control system 12: the total flow rate of cooling water for the large surface is 1000L / h, and the total flow rate of cooling water for the small surface is 500L / h; the initial casting speed is 30mm / min, and after the casting flow is stable, it is increased to 60mm / min for continuous and stable casting.
[0054] 6. Gradient cooling solidification After leaving the forming mold 9, the slab enters the secondary cooling device 13. The cooling water control system 12 sets the total flow rate of the secondary cooling water to 400L / h. The cooling sequence is as follows: first, the surface of the slab is rapidly solidified and shaped by the spray cooling component 1301, and then the heat in the core of the slab is slowly released by the air cooling mechanism 1302, gradually reducing the overall temperature to avoid cracks and deformation caused by excessive temperature difference between the inside and outside of the thick slab. Finally, a copper-titanium alloy slab with a thickness of 180mm and a width of 550mm is formed.
[0055] 7. Finished Product Inspection Results Samples were taken from the head, middle and tail sections along the length of the slab for composition analysis: the Ti content at the three locations was 3.34%, 3.31% and 3.31% respectively, showing excellent compositional uniformity; the oxygen content was 0.0010%, 0.0008% and 0.0009% respectively, and the nitrogen content was 0.0001% for all samples, indicating that the melt cleanliness meets the requirements for use in high-elasticity components.
[0056] Example 2 This embodiment provides a method for preparing copper-titanium alloy slabs using the above-described apparatus, including: It should be noted that the following steps differ from those in Example 1; the remaining steps are the same: 1. Pre-treatment of equipment before production Preheating of the flow channel: The difference from this step in Example 1 is that the baking preheating device 10 is set to 280°C and baked at a constant temperature for 3.5 hours, and then kept preheated after completion; A comprehensive inspection of the vacuum melting device 1, including the vacuum, heating, stirring, feeding, and sealing systems; and debugging of the gas supply system 11 and all water circuits, air cooling, and spray components of the cooling and solidification device 4.
[0057] 2. Ingredient preparation and feeding The base material is 99.9935% Grade A electrolytic copper. A copper-titanium master alloy with a Ti content of 50% is selected. The raw materials are weighed according to the target Ti content of 3.4wt% and the balance Cu. The Grade A electrolytic copper is loaded into the melting furnace chamber of the vacuum melting device 1, and the master alloy is sealed and stored in the feeding box 8.
[0058] 3. Vacuum stepped heating smelting The vacuum pumping system 6 stabilizes the furnace chamber pressure to 8 Pa; the stepped power controllable induction heating system 7 operates in segments: the initial power is set to 38% of the total power, and the temperature is held for 18 minutes → the power is increased to 58% of the total power, and the temperature is held for 14 minutes → the power is increased to 78% of the total power and the heating continues until the cathode copper is completely melted.
[0059] 4. Alloying, refining and electromagnetic stirring After the intermediate alloy is completely melted, the melt temperature stabilizes at 1320℃, and the refining time is 38 minutes. Then, the electromagnetic stirring mechanism 5 is started for stirring, with a stirring power of 12kW, and stirring is carried out for 14 minutes.
[0060] 5. Tundish-free direct-connection inert atmosphere continuous casting Argon gas is introduced through the gas supply system 11, with a stable flow rate of 12L / min; the melt enters the forming mold 9 directly through the guide channel 2, which is preheated at 280℃ for 3.5h; the cooling water control system 12 is set with a total cooling water flow rate of 1100L / h for the large surface and 550L / h for the small surface, and a stable casting speed of 70mm / min.
[0061] 6. Gradient cooling solidification The total flow rate of secondary cooling water is controlled at 450L / h. The slab is successively cooled by spray cooling and air cooling in stages, and finally cast into a copper-titanium alloy slab with a thickness of 190mm and a width of 580mm.
[0062] 7. Finished Product Inspection Results Samples were taken from the head, middle, and tail sections along the length of the slab for composition analysis: the Ti content in the head, middle, and tail sections of the slab was 3.36%, 3.34%, and 3.31%, respectively; the oxygen content was 0.0005%, 0.00053%, and 0.0007%, respectively; and the nitrogen content was 0.0001% in all sections. The impurity gas content was low, and the elemental distribution showed little fluctuation.
[0063] Example 3 This embodiment provides a method for preparing copper-titanium alloy slabs using the above-described apparatus, including: It should be noted that the following steps differ from those in Example 1; the remaining steps are the same: 1. Pre-treatment of equipment before production Preheating of the guide channel: The baking preheating device 10 is heated to 300℃ and baked at a constant temperature for 4 hours; A comprehensive inspection of the entire preparation equipment confirmed that the vacuum system, electromagnetic stirring mechanism 5, protective gas supply, and primary and secondary cooling systems were all operating stably.
[0064] 2. Ingredient preparation and feeding The raw materials were weighed based on the following formula: 99.9935% Grade A electrolytic copper and 52% Ti copper-titanium master alloy. The weight of each raw material was calculated based on the 3.3 wt% Cu balance of the target Ti content in the finished product.
[0065] 3. Vacuum stepped heating smelting Vacuum was drawn to a furnace chamber pressure of 6 Pa; the stepped power controllable induction heating system operated in 7 segments: the initial power was set to 40% of the total power, held for 20 minutes → the power was increased to 60% of the total power, held for 15 minutes → the power was increased to 80% of the total power and heated until the solid copper material was completely melted.
[0066] 4. Alloying, refining and electromagnetic stirring After the intermediate alloy is melted and the melt temperature is stabilized at 1300℃, the refining time is 40min; the power of the electromagnetic stirring mechanism 5 is adjusted to 15kW, and the melt is continuously stirred for 15min to fully mix the melt.
[0067] 5. Tundish-free direct-connection inert atmosphere continuous casting Argon flow rate is adjusted to 15L / min to prevent air oxidation; the melt is directly introduced into the forming mold 9 through the guide channel 2 which is baked at 300℃ for 4 hours; the cooling water control system 12 is set to a total cooling water flow rate of 1200L / h for the large surface and 600L / h for the small surface, and the casting speed is stabilized at 80mm / min.
[0068] 6. Gradient cooling solidification The total flow rate of secondary cooling water is 500L / h. The slab is cooled in a gradient manner by spray cooling components and air cooling mechanism to form a large copper-titanium alloy slab with a thickness of 200mm and a width of 600mm.
[0069] 7. Finished Product Inspection Results Composition analysis was performed on samples taken from the head, middle, and tail sections along the length of the slab: the Ti content in the head, middle, and tail sections was 3.31%, 3.30%, and 3.29%, respectively; the oxygen content was 0.0011%, 0.0009%, and 0.0010%, respectively; and the nitrogen content was 0.0001% in all sections. Figure 3 The SEM microstructure observation shown revealed that the number of pores inside the billet was extremely small, with no macroscopic or microscopic segregation defects. The alloy second phase was fine and uniformly dispersed, resulting in the best overall billet quality.
[0070] Example 4 This embodiment provides a method for preparing copper-titanium alloy slabs using the above-described apparatus, including: It should be noted that the following steps differ from those in Example 1; the remaining steps are the same: 1. Pre-treatment of equipment before production Preheating of the guide channel: The baking preheating device 10 is set to 220℃ and baked at a constant temperature for 2.5 hours, maintaining the preheated state for later use; Check each item in the vacuum melting, heating and stirring, argon supply, and cooling system pipelines and control components to eliminate potential leaks and jamming.
[0071] 2. Ingredient preparation and feeding The base material is 99.9935% Grade A electrolytic copper, combined with a copper-titanium master alloy with a Ti content of 53%. The raw materials are weighed according to the target Ti content of the finished product and the remaining Cu content of 3.5wt%.
[0072] 3. Vacuum stepped heating smelting The vacuum pumping system 6 stabilizes the pressure in the melting chamber to 10Pa; the stepped power controllable induction heating system 7 operates in segments: the initial power is set to 30% of the total power, and the temperature is held for 10 minutes → the power is increased to 50% of the total power, and the temperature is held for 10 minutes → the power is increased to 70% of the total power and the heating continues until the cathode copper is completely melted.
[0073] 4. Alloying, refining and electromagnetic stirring After the intermediate alloy is completely melted, the melt temperature stabilizes at 1250℃, and the refining time is 30 minutes. Then, the electromagnetic stirring mechanism 5 is started with a stirring power of 8kW and a stirring time of 10 minutes to eliminate local titanium enrichment in the melt.
[0074] 5. Tundish-free direct-connection inert atmosphere continuous casting The argon flow rate is adjusted to 8L / min to continuously build an inert protective layer inside the molding die; after the melt is preheated at 220℃ for 2.5h, it enters the graphite composite molding die 9 through the guide channel; the cooling water control system 12 is set to a total flow rate of 900L / h for the large surface cooling water and 450L / h for the small surface cooling water, and the casting speed is stabilized at 50mm / min.
[0075] 6. Gradient cooling solidification The total flow rate of the secondary cooling water was adjusted to 350L / h. The slab was first sprayed with a surface layer for shaping, and then air-cooled to slowly release the internal heat, finally producing a copper-titanium alloy slab with a thickness of 170mm and a width of 520mm.
[0076] 7. Finished Product Inspection Results The chemical composition of the prepared slab was analyzed, and the results are shown in Table 1. The Ti content in the head, middle, and tail of the slab was 3.35%, 3.33%, and 3.36%, respectively; the oxygen content was 0.0008%, 0.0009%, and 0.0007%, respectively; and the nitrogen content was 0.0001% in all three parts. The product has uniform composition and high purity.
[0077] Comparative Example 1 This comparative example uses the same raw material ratio as Example 1 to ensure a single variable and objectively compare the performance differences between the traditional process and the tundish-free integrated continuous casting process of this application. Raw material ratio: 99.9935% Grade A electrolytic copper is used, combined with a copper-titanium master alloy with a Ti mass fraction of 48%. The target finished product has a Ti element mass fraction of 3.3 wt%, with the balance being copper. The overall process flow is: conventional vacuum melting → traditional ingot casting → heat-holding forging → multiple hot rolling blanking → finishing to obtain the finished slab. The specific process steps are as follows: 1. Conventional vacuum melting process Weigh the Grade A electrolytic copper and copper-titanium master alloy according to the specified ratio. Place the electrolytic copper inside the vacuum melting furnace chamber, and store the master alloy separately. Evacuate the melting chamber to 5 Pa and heat it using a conventional constant high-power heating mode until the electrolytic copper is completely melted. Then, add the copper-titanium master alloy and heat it to 1280℃ after the alloy is completely melted. Perform conventional static refining for 35 minutes without applying electromagnetic stirring. The copper-titanium alloy melt is obtained after the melting is complete.
[0078] 2. Traditional ingot casting process After melting, the alloy melt is transferred through a conventional tundish to a square cast iron ingot mold for natural casting. The casting process is not protected by a continuous inert gas seal; oxidation is initially prevented only by the vacuum environment of the furnace chamber. The melt is allowed to cool and solidify naturally within the mold, without any gradient temperature control. After cooling to room temperature, it is demolded to obtain a square copper-titanium alloy ingot with a diameter of 220 mm and a length of 650 mm. After demolding, the surface oxide scale and burrs are removed from the ingot for later use.
[0079] 3. High-temperature insulation pretreatment process The ingot is placed in an industrial heating furnace for uniform heating at a set temperature of 880–920℃, and held at this temperature for 2.5 hours to ensure uniform temperature throughout the ingot, reduce forging stress, and prevent cracking defects during forging. After the holding period, the ingot is quickly removed and immediately put into the forging process, minimizing air cooling and secondary oxidation time.
[0080] 4. Free forging billet preparation process A high-temperature ingot, after being held at room temperature, is forged using a high-speed forging press. The forging pressure is controlled at 800–1000 t, employing a multi-pass reciprocating forging process. First, upsetting forging is performed to compress the axial dimension and increase the radial dimension of the ingot, with a single reduction controlled at 15%–20%. Then, elongation forging is performed, reciprocating to shape the ingot, repeating the forging process 6–8 times to gradually break down the coarse solidified structure inside the ingot and initially eliminate casting porosity defects. If the ingot temperature drops below 750℃ during forging, it needs to be reheated in the furnace and forged again, ultimately resulting in a forged billet with a thickness of 240 mm, a width of 620 mm, and a length of 420 mm.
[0081] 5. Multi-pass hot rolling forming process The forged billet was then fed back into the heating furnace and held at a constant temperature of 850℃ for 1.5 hours. After holding, it was sent to a hot rolling mill for multi-pass rolling to form the billet. A progressive thinning rolling process was adopted, with a total of 10-12 rolling passes, a single-pass reduction of 8%-12%, and a rolling speed of 1.2-1.8 m / s. Through repeated rolling in multiple passes, the thick forged billet was gradually rolled into a slab of the target specifications. The rolling process was carried out without sealed inert protection, and the slab surface was continuously exposed to air, resulting in oxidation. After rolling, the slab was air-cooled to remove surface oxide scale and edge defects, ultimately yielding a copper-titanium alloy slab with a thickness of 180 mm and a width of 550 mm, consistent with the specifications of the finished product in Example 1. Test results showed that the Ti content at the head, middle, and tail of the slab was 3.64%, 3.29%, and 3.38%, respectively, indicating severe compositional segregation. The oxygen contents were 0.0042%, 0.0047%, and 0.0030%, respectively, which were significantly higher than those in the above embodiments of this application, indicating that traditional processes are difficult to effectively control oxidation problems.
[0082] Comparative Example 2 Copper-titanium alloy slabs were prepared using a vacuum melting-tundish-continuous casting process, which is a standard technique. The raw material ratios and process parameters were the same as in Example 1, but a tundish was placed between the vacuum melting furnace and the crystallizer.
[0083] The test results showed that the Ti content at the head, middle, and tail of the slab was 3.35%, 3.42%, and 3.30%, respectively, and the oxygen content was 0.024%, 0.0058%, and 0.0009%, respectively. The abnormally high oxygen content at the head indicates that the tundish structure caused severe secondary oxidation of the melt during transport, affecting the stability of product quality.
[0084] Table 1. Results of ingot composition analysis for examples and comparative examples.
[0085] The test results in Table 1 clearly show that the copper-titanium alloy slabs prepared in Examples 1-4 have the following significant advantages: Good compositional uniformity: The titanium content deviation of the head, middle and tail of the slab in each embodiment is less than 0.07%, while the deviation of Comparative Example 1 reaches 0.35%, indicating that this application effectively solves the compositional segregation problem through electromagnetic stirring and precise process control.
[0086] Extremely low oxygen content: The oxygen content in the embodiments of this application is controlled within the range of 0.0005%-0.0011%, while that in Comparative Example 1 is 0.0030%-0.0047%, and that in Comparative Example 2 is even as high as 0.024%. This fully demonstrates the excellent effect of the vacuum melting-tundish-free direct continuous casting process of this application in preventing melt oxidation.
[0087] Low impurity content: The carbon, sulfur and other impurity content in the embodiments of this application are significantly lower than those in the comparative example, further demonstrating the high cleanliness advantage of the process of the present invention.
[0088] pass Figure 3 Microscopic observation also confirms that the copper-titanium alloy slab prepared by this invention has a dense structure, few pores, and no defects such as macroscopic segregation or microscopic segregation. The second phase is fine and uniformly distributed, which fully meets the material quality requirements of high-end applications.
[0089] The above are merely preferred embodiments of this application and do not limit the patent scope of this application. Any equivalent structural or procedural transformations made using the content of this application's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of this application.
Claims
1. A method for preparing a copper-titanium alloy slab, characterized in that, Includes the following steps: The raw materials are added in batches, one furnace at a time, and include cathode copper and copper-titanium master alloy. The cathode copper is placed in the melting chamber, and the melting chamber is evacuated to a pressure of 0.1 Pa to 10 Pa. The chamber is heated using a stepped heating power control method until the cathode copper is completely melted to obtain a melt. The copper-titanium master alloy is added to the melt. When the master alloy melts completely and the temperature rises to 1250℃-1350℃, it is refined for 10-30 minutes. After refining, the mixture is stirred to obtain an alloy melt. The alloy melt is then introduced into a forming mold through a guide channel and continuously cast under an inert gas protective atmosphere to obtain a slab. The total flow rate of cooling water on the large surface, the total flow rate of cooling water on the small surface, and the total flow rate of secondary cooling water of the forming mold are controlled to allow the slab to gradually cool and solidify, thereby obtaining the copper-titanium alloy slab.
2. The method for preparing copper-titanium alloy slabs according to claim 1, characterized in that, The stepped heating power control method includes: the initial heating power is 30%-40% of the total power, after holding the temperature for 10-20 minutes, the power is increased to 50%-60% of the total power, held for 10-15 minutes, and finally the power is increased to 70%-80% of the total power until the material is completely melted.
3. The method for preparing copper-titanium alloy slabs according to claim 1, characterized in that, The refining process employs an electromagnetic stirring device with a stirring power of 5kW-15kW and a stirring time of 5-10 minutes.
4. The method for preparing a copper-titanium alloy slab according to claim 1, characterized in that, The flow channel is pre-baked at a temperature of 200℃-300℃ for 2-4 hours.
5. The method for preparing a copper-titanium alloy slab according to claim 1, characterized in that, The inert gas is argon or helium, and the flow rate of the inert gas introduced into the molding die is controlled to be 5L / min-15L / min.
6. The method for preparing a copper-titanium alloy slab according to any one of claims 1-5, characterized in that, The total flow rate of cooling water for the large surface of the molding die is controlled at 800L / h-1200L / h, and the total flow rate of cooling water for the small surface is controlled at 400L / h-600L / h.
7. The method for preparing a copper-titanium alloy slab according to claim 6, characterized in that, The total flow rate of the secondary cooling water is controlled at 300L / h-500L / h, and the slab solidification is gradually cooled by spray cooling and air cooling in sequence.
8. The method for preparing a copper-titanium alloy slab according to claim 6, characterized in that, The purity of the cathode copper is ≥99.95%, and the titanium content in the copper-titanium master alloy is 20wt%-30wt%.
9. An apparatus for preparing a copper-titanium alloy slab, used to implement the method for preparing a copper-titanium alloy slab according to any one of claims 1-8, characterized in that, It includes a vacuum melting device, a continuous casting forming device, and a cooling and solidification device. The outlet of the vacuum melting device is directly connected to the inlet of the continuous casting forming device through a guide channel. The continuous casting forming device includes a graphite forming mold and an argon gas protection system.
10. The apparatus for preparing copper-titanium alloy slabs according to claim 9, characterized in that, The flow channel is equipped with a baking preheating device, the molding die is connected to a cooling water control system and a secondary cooling device, and the vacuum melting device is equipped with an electromagnetic stirring device.
